Lean Service Design in Purchasing Order of Motorcycles: Case Study at Mandiri Utama Finance Branches Tangerang, Indonesia - Rizky Artadi; Tantri Yanuar Rahmat Syah (Penerbit Kemala Indonesia, 2019)
Finance non-bank (leasing) is a private company that have services to measure the performance of non-financial behaviour employees, ability employees, and customer satisfaction. This company can be determined with the performance combination in internal and external company over leasing. The internal factors are owned to combined by external factors over owned company. Here, we analyse service of by PT. Mandiri Utama Finance to consumers over credit financing motorcycle or cars property. The consumers of Mandiri Utama Finance joined a dealer to buy the motorcycle or cars. On the other hand, consumers (as a dealer) was nominated for buyers motorcycle or cars. Thus, inside of PT. Mandiri Utama Finance is a surpass competition between company leasing, and purchasing process to order from dealer to PT. Mandiri Utama Finance. The effort to increased quality from services of customer satisfaction, the companies need to measuring the degree of quality per-years. One of them are applied over methods and lean service. The Lean service at this research are applied to asses concept and method lean six sigma over PT. Mandiri Utama Finance with methodology namely DMAIC (Define, Measure, Analyse, Improve and Control)